Critical Thinking Skills of Slow Learners in Mathematical Problem-Solving: A Systematic Literature Review - Sulfiati; Irwan Akib; Muhammad Muzaini (MASI Mandiri Edukasi, 2025)
Although much research has highlighted slow learners' difficulties in learning mathematics, most studies have focused only on the final learning outcomes without delving into the thinking processes during problem-solving. The lack of research on the cognitive steps slow learners take to develop critical thinking skills creates a gap in the literature that needs to be filled. The article examines the connection between the